Multivariate Analysis ANOVA Based Distribution of Nitrogen Dioxide in Lampung Barat And Way Kanan Regencies - Trina, Innamaa; Mutawakkilah, Qudwah; Rinawati, Rinawati; Satria, Heri; Kiswandono, Agung Abadi (Department of Chemistry Faculty of Science and Technology Walisongo, 2023)
The rise of construction projects and population growth, followed by the expansion of industry and any other sectors such as housing estate, offices, and transportation, can lead to not only economic growth but also negative impacts such as air pollution, including nitrogen dioxide (NO2) pollutants. According to KEP-45/MENLH/10/1997, air pollution can be determined by The Pollutant Standards Index (PSI). The statistical analysis result employing the multivariate ANOVA test with the Anderson-Darling method showed the impact of NO2 concentrations on four location points over two years. Meanwhile, the data result of PSI revealed a high level of ambient air NO2 in Lampung Barat Regency, particularly at the monitoring point of offices. On the other hand, in Way Kanan Regency, the level of ambient air NO2 tends to be safe and secure at the monitoring point of industry and transportation. The factor of sampling location and technique (stage 1: dry season, stage 2: rainy season) did not give a significant effect on the NO2 level due to a p-value ≥ 0,05. However, the sampling point (of monitoring) influenced the NO2 level for p-value ≤ 0,05 in Lampung Barat and Way Kanan Regency in 2019-2020 which was still claimed as safe and secure based on PP No. 41 in the Year 1999, which sets the required limit at 100 g/m3.